Processing Pengolahan Limbah Kotoran Sapi Menjadi Pupuk Organik untuk Perbaikan Kualitas Lingkungan Desa Seputih Kecamatan Mayang Kabupaten Jember - Ika Purnamasari; Suci Ristiyana; Yagus Wijayanto; Tri Wahyu Saputra (Universitas Mataram, 2022)
Seputih Village is one of the villages in Mayang District, Jember Regency. In addition to the agricultural sector, the livestock sector is also the mainstay of the village, namely cattle with almost 70% of households owning livestock. The high number of cattle in the community causes an increase in the amount of livestock manure produced. One solution that can be applied to reduce this waste is by processing manure into solid organic fertilizer so that the community service program implemented in Seputih Village is the manufacture of solid organic fertilizer from cow dung that can be utilized by the community on agricultural land. Activities carried out to achieve the objectives include coordination meetings of the lecturer team with village heads, farmers and ranchers; potential survey; training on the manufacture of solid organic fertilizers as well as monitoring and evaluation. The community service activity was enthusiastically welcomed. The community directly received information on the importance of handling cow dung waste and had experience in making organic fertilizer workshops. Solid organic fertilizer can be used after two weeks of the fermentation process.